Second Trimester Dilation (Global Journal of Medical Research, 2020)
Uterus didelphys is one of the rarest of the Mullerian duct anomalies and can lead to unique obstetric and gynecologic outcomes and considerations. This case describes a patient with known uterus didelphys and intact longitudinal vaginal septum who desired termination of pregnancy at 17 weeks gestation due to fetal anomaly. She underwent dilation and evacuation (D
Keywords: didelphys; dilation and evacuation; termination; Mullerian anomaly